Foucault on the politics of parrhesia - Dyrberg, Torben Bech; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
Foucault saw the notion of parrhesia (truth-telling) as the most important factor for how governments could and should communicate with their people and vice versa. This important collection compiles and analyses Foucault's views on parrhesia to shed new light on his ideas on the importance of truth-telling in democracies.
Keywords: Science; Science; Science, general